The influence of McKenzie’s method in the treatment of low back pain - Sousa, Vanessa Paula de; Moura, David Reis; Cunha, Francisco Valmor Macedo da (Manual Therapy, Posturology & Rehabilitation Journal, 2016)
Introduction: Low back pain, due to the high prevalence, is the main reason for sickness and pensions in Brazil causing a major burden for the state and the reduction of the individual’s quality of life. The treatment may be conservative (drug and therapy) or surgery, but often such treatments are not definitive and culminating in reincidivas. Among the physiotherapy intervention techniques, Mckenzie method stands out because it is an individualized intervention technique that emphasizes patient education through exercises to restore normal function, where the patient learns to avoid during treatment movements, postures and activities that worsen your condition. Objective: This study aimed to investigate the effect of Mckenzie method on the treatment of lumbar. Methods: We performed a literature search of articles published between 2005 to 2015, in Portuguese, English and French, using the key words low back pain, quality of life and physical therapy in Scienciedirect databases, Peter, Pubmed, LILACS and scielo. Results and conclusion: The articles were initially screened for the content of the titles and abstracts and confronted the inclusion and exclusion criteria. Subsequently, the selected articles were analyzed in all content and data were organized into figures and framework to present the main findings of the research. Publications on the theme revealed the importance of McKenzie in the reduction of pain symptoms and disability in low back pain, contributing to the patient’s return in their activities of daily living.